2008
DOI: 10.2478/s11756-008-0153-5
|View full text |Cite
|
Sign up to set email alerts
|

Classification of mesic and wet grasslands in northwest Croatia

Abstract: In this paper, 450 relevés of grassland vegetation of the Molinio-Arrhenatheretea class in northwest Croatia have been classified using the agglomerative Ward's Method in the PC-ORD program. In the process of classification, the following seven groups were obtained: 1. Bromus erectus-Arrhenatherum elatius, 2. Arrhenatherum elatius, 3. Crepis biennisArrhenatherum elatius, 4. Luzula campestris-Holcus lanatus, 5. Deschampsia cespitosa-Betonica officinalis, 6. Equisetum palustre, 7. Oenanthe silaifolia-Alopecurus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…The presence of the species Cynodon dactylon indicates the more southern and warmer character of these stands compared to this type of vegetation in Central Europe. The position of Bromo‐Cynosuretum is unclear; according to (Stančić ) characteristic species have a broad ecological range and should be divided into a number of associations. In our analysis, these stands (together with some wet Arrhenatherion elatioris stands) are separated as a single cluster with a transitional position between Cluster 5 and 10 in the DCA diagram (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the species Cynodon dactylon indicates the more southern and warmer character of these stands compared to this type of vegetation in Central Europe. The position of Bromo‐Cynosuretum is unclear; according to (Stančić ) characteristic species have a broad ecological range and should be divided into a number of associations. In our analysis, these stands (together with some wet Arrhenatherion elatioris stands) are separated as a single cluster with a transitional position between Cluster 5 and 10 in the DCA diagram (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…). Stančić () indicated that some of the relevés of Bromo‐Cynosuretum should be classified into Arrhenatherion elatioris and some into Deschamspion cespitosae .…”
Section: Discussionmentioning
confidence: 99%
“…), also from the Netherlands. Small former river meanders crossing the site have an even more flood‐tolerant species association, of the Calthion alliance, which resembles the Oenanthe silaifolia‐Alopecurus pratensis association of Stančić () from Central Europe. In 2003, four 150‐m long transects were set out across a slope topography, along each of which 11,1 m × 1 m quadrats were placed.…”
Section: Methodsmentioning
confidence: 93%
“…Areas of the meadow subject to longer periods of inundation contain a less species-rich community, whose closest continental counterpart is the Sanguisorbo-Silaetum (Schaminée et al 1996), also from the Netherlands. Small former river meanders crossing the site have an even more flood-tolerant species association, of the Calthion alliance, which resembles the Oenanthe silaifolia-Alopecurus pratensis association of Stančić (2008) from Central Europe. In 2003, four 150-m long transects were set out across a slope topography, along each of which 11,1 m 9 1 m quadrats were placed.…”
Section: Field Study Methodsmentioning
confidence: 94%
“…Abandoned grasslands are subject changes in their floristic composition, ecology and syntaxonomy (Meshinev et al 2000, Jantunen 2003, Stránská 2004, Velev & Apostolova 2008, Ruprecht et al 2009, Rusina & Kiehl 2010, Házi et al 2011, Priede 2011. When such changes occur in vegetation, some grassland types may locally disappear (Stančić 2008, Hegedüšová & Senko 2011. These changes in the vegetation are also reflected in other components of biodiversity, such as insects (Söderström et al 2001, Wiezik et al 2011, Šumpich & Konvička 2012, birds (Nikolov 2010), etc.…”
Section: Introductionmentioning
confidence: 99%